The Application of The Jigsaw Method to Increase Student Learning Motivation in Class XI.F SMAN 1 Suliki 2024 - Dasril Effendi (BiCED Proceeding, 2024)
This study aims to examine the effect of applying the jigsaw cooperative learning model on the learning motivation of class XI students at SMAN 1 Suliki. This research uses a classroom action research (CAR) approach with two cycles, each consisting of planning, implementation, observation, and reflection stages. The results of the study indicate an increase in student learning motivation, with the motivation percentage in the first cycle reaching 70.8%, an increase of 11.4% compared to the pre-cycle results. The applied jigsaw method had a positive impact on increasing student activity and enthusiasm in the learning process, although there were challenges in the initial understanding of this method. Overall, the implementation of the jigsaw method can enhance students' learning motivation, particularly in Islamic Religious Education (PAI) learning, as evidenced by increased learning outcomes and student enthusiasm.